Critical role of microglial CD40 in the maintenance of mechanical hypersensitivity in a murine model of neuropathic pain - Cao, Ling (2009)
We recently demonstrated a contributing role of spinal cord infiltrating CD4(+) T lymphocytes in the maintenance of mechanical hypersensitivity in a rodent model of neuropathic pain, spinal nerve L5 transection (L5Tx). It has been demonstrated that microglia play a role in the etiology of pain states. We hypothesized that infiltrating CD4(+) T lymphocytes communicate with microglia via a CD40-CD154 interaction. Here, we investigated the role of CD40 in the development of mechanical hypersensitivity post-L5Tx. CD40 KO mice displayed significantly decreased mechanical sensitivity compared with WT mice starting from day 5 post-L5Tx. Using bone marrow chimeric mice, we further identified a pro-nociceptive role of CNS microglial CD40 rather than the peripheral leukocytic CD40. Flow cytometric analysis determined a significant increase of CD40(+) microglia in the ipsilateral side of lumbar spinal cord post-L5Tx. Further, spinal cord proinflammatory cytokine (IL-1β, IL-6, IL-12, and TNF-α) profiling demonstrated an induction of IL-6 in both WT and CD40 KO mice post-L5Tx prior to the increase of microglial CD40 expression, indicating a CD40-independent induction of IL-6 following L5Tx. These data establish a novel role of microglial CD40 in the maintenance of nerve injury-induced behavioral hypersensitivity, a behavioral sign of neuropathic pain.